(untitled) (L’uomo nero. Materiali per una storia delle arti della modernità, 2022)
The first issue of «L’uomo nero» was published in 2003 and the journal is now facing a major change, passing from printed to online edition, in open access. To celebrate this passage, an anthological issue is presented which collects a selection of contributions published over the years by the members of the Scientific Committee and some old friends of «L’uomo nero». The choice of fourteen articles among the more than two hundred and forty published may not be fully representative of the physiognomy of the journal, but may at least serve to give a summary of the meaning of its project.